Identifying Patterns in Financial Markets New Approach Combining Rules Between PIPs and SAX - Leitão, João (SpringerBriefs in Computational Intelligence,, 2018)
This book describes a new pattern discovery approach based on the combination among rules between Perceptually Important Points (PIPs) and the Symbolic Aggregate approximation (SAX) representation optimized by Genetic Algorithm (GA). The proposed approach was tested with real data from S&P500 index and all the results obtained outperform the Buy&Hold strategy. Three different case studies are presented by the authors.